Issues of European monetary integration - Heinrich Matthes (Intereconomics, 1985)
In recent years significant progress has been made towards European monetary integration. Widespread agreement as to the role of monetary policy has been established and there were no realignments of exchange rates within the European Monetary System between March 1983 and July 1985. This was the longest period without realignment in the EMS and contrasted sharply with the six realignments observed in the four years previously. What are the prospects for the further strengthening of the EMS? How can the present system be developed further?
Keywords: 330; European Community